Process simulation and sensitivity analysis of indirect coal gasification using aspen plus® model - Uddin, F. (Asian Research Publishing Network, 2016)
A steady state Aspen Plus® simulation is used to propose and analyse a novel indirect gasification model using steam as the gasifying medium. A sensitivity study is carried out by varying the steam-to-coal ratio. Part of the Syngas produced is combusted in the furnace to provide flue gases at high temperature which is then passed through the bayonets to provide reaction heat. RK-Soave method is used for the evaluation of physical properties of mixed conventional components and CISOLID components in the simulation. The feedstock used in the simulation is indigenous Thar coal from Pakistan, where large coal reserves are present. It was found that a lower steam-to-coal ratio increases the heat content of the syngas produced. Also, the carbon conversion undergoes a maximum at the ratio 2.0. As we increase the steam-to-coal ratio, the yields are better but inevitably reduce the quality of syngas produced. Carbon conversions and H2/CO ratios as high as 95.76 and 3.09 respectively were observed with higher steam to carbon ratios. However, lower ratios provide high yields (69.00) and cold gas efficiencies (54.41). Based on these results, it can be said that this parameter significantly influences the syngas quality and processing costs and the diversity of trends suggest a more detailed analysis for optimisation of the process. © 2006-2016 Asian Research Publishing Network (ARPN).